Desafíos éticos en la gestión de servicios de salud mental en Ecuador. - Quevedo Barberán, Marcos Joe (My University, 2025)
The ethical challenges inherent in mental health management in Ecuador highlight a fundamental tension between patients' human rights and the limitations of the healthcare system, especially regarding autonomy, which is frequently violated through involuntary admissions and treatment without informed consent. Modern legislation is crucial to protecting these rights, although its implementation can generate conflicts with the provision of care. The paper delves into the specific challenges presented in Ecuador, such as limitations on respect for autonomy due to a shortage of professionals and stigma, the need to strengthen informed consent, the importance of confidentiality, the multidimensional view of patient autonomy and capacity, and the impact of stigma and discrimination on access to mental health services.
Los desafíos éticos inherentes a la gestión de salud mental en Ecuador, se destaca una tensión fundamental entre los derechos humanos de los pacientes y las limitaciones del sistema sanitario, especialmente en lo referente a la autonomía, frecuentemente vulnerada en admisiones involuntarias y tratamientos sin consentimiento informado. La legislación moderna es crucial para proteger estos derechos, aunque su implementación puede generar conflictos con la provisión de atención. Se profundiza en los desafíos específicos presentados en Ecuador, como las limitaciones al respeto a la autonomía por la escasez de profesionales y el estigma, la necesidad de fortalecer el consentimiento informado, la importancia de la confidencialidad, la visión multidimensional de la autonomía y capacidad del paciente, el impacto del estigma y la discriminación en el acceso a los servicios de salud mental.
Keywords: AUTONOMÍA; CONSENTIMIENTO INFORMADO; ESTIGMA; ACCESO EQUITATIVO